Effects of selenium supplementation on cardiometabolic risk factors, inflammatory, and antioxidant markers: A systematic review and meta-analysis protocol - Shirin Djalalinia; Mahnoosh Khosravi; Motahareh Hasani; Sahar Saeedi Moghaddam; Mehrdad Kazemzadeh Atoofi; Armita Mahdavi-Gorabi; Mehdi Noroozi; Mostafa Qorbani; Hamid Asayesh; Ali Soleimani (International Journal of Preventive Medicine, 2019)
Background: Selenium (Se) is considered as an antioxidant trace element involved in key activities in human metabolism. Recent investigations indicate that Se plays a pivotal role in human health. Se supplementation considered as an intervention is both cost-effective and simple-to-use that may play an important role in the prevention of cardiometabolic risk factors (CRFs), inflammatory, and antioxidant markers. Methods: This paper is a protocol study on systematic review of probable effects of Se supplementation on CRFs, inflammatory, and antioxidant markers. The aim was to achieve three international databases available related to the current publications including, PubMed, ISI/WOS, and Scopus. We attempted to search for randomized clinical trials (RCT) and cross-over trials pertaining to human subjects without any restriction on language and time. In addition, there was no limitation on the age of participants. For RCTs were included all studies in different target groups comprising diabetic patients, patients with polycystic ovarian syndrome, obese subjects, or even healthy controls. To investigate the effect of Se, we included all studies which Se is used either as single therapy or as combination therapy. All studies associated with articles and meta-analyses would be evaluated to review their references. Conclusions: The current study contained numerous outcomes. The result of this study can be led to make reliable scientific evidence on the probable effects of Se supplementation on CRFs, inflammatory factors, and antioxidant factors. In addition to these findings, other technical documents developed for a systematic review can be used for future studies.